2019
DOI: 10.3892/ol.2019.10356
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of insulin‑like growth factor 1 signaling synergistically enhances the tumor suppressive role of triptolide in triple‑negative breast cancer cells

Abstract: Triptolide (TPL) is an active extract from a Chinese herb, which has been used for centuries in China. TPL exhibits numerous bioactivities and pharmacological effects, including antitumor, anti-inflammatory and immunosuppressive activities. However, previous studies have further revealed a multi-target toxicity of TPL, including reproductive toxicity, hepatotoxicity and renal cytotoxicity. To validate the clinical benefit and reduce the risk of TPL application, studies have investigated the combination of TPL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Powell et al ( 52 ) demonstrated that the commonly inherited IGF1R variant (rs2016347) reduces breast cancer risk by enhancing mammary gland involution. In addition, triptolide and IGF1R inhibitor (AG1024) can synergistically inhibit the proliferation and induce the apoptosis of triple-negative breast cancer cells ( 53 ). These studies indicated that IGF1R serve some essential roles in the occurrence and development of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Powell et al ( 52 ) demonstrated that the commonly inherited IGF1R variant (rs2016347) reduces breast cancer risk by enhancing mammary gland involution. In addition, triptolide and IGF1R inhibitor (AG1024) can synergistically inhibit the proliferation and induce the apoptosis of triple-negative breast cancer cells ( 53 ). These studies indicated that IGF1R serve some essential roles in the occurrence and development of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…TP is a small molecule compound with antitumor, antiangiogenic, anti-inflammatory, and proapoptotic properties [13]. It is found that TP exerts strong inhibitory effect on the biological processes of liver [14,15], ovarian [16][17][18][19], lung [20][21][22], gastric [23,24], and breast [25,26] cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is a small molecule compound with anti-tumor, anti-angiogenesis, anti-inflammatory and pro-apoptotic effects [8]. TP has anti-cancer effect against liver [9,10], ovarian [11][12][13][14], lung [15][16][17], gastric [18,19], breast [20,21].…”
Section: Introductionmentioning
confidence: 99%